2008
DOI: 10.1134/s1061934808030088
|View full text |Cite
|
Sign up to set email alerts
|

Simple spectrophotometric method for the determination of sulfur dioxide by its decolorizing effect on the peroxovanadate complex

Abstract: 1 volumetric [6, 19] as well as other methods [12-16] when sulfur dioxide is in low concentrations, because of its simplicity and cost-effective instrumentation. However, one of the spectrophotometric methods [20] employs rosaniline and formaldehyde, which are considered to be toxic [21]. Another AOAC method [22] requires the use of the dye thymol blue, a known pH indicator. Obviously, the method requires the strict control of pH and also suffers from a narrow range of sulfur dioxide determination. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Furthermore, the formation of 1 O 2 by spontaneous disproportionation of O 2 •– has long been proposed (R10a–b) . Quantitative determination in the literature revealed that less than 10% of the O 2 produced was in the singlet state, suggesting that this might be an inefficient pathway for 1 O 2 evolution. , In order to confirm the critical role of H 2 O 2 in the PDS system, the presence of H 2 O 2 in PDS dark and PDS light was determined following a spectrophotometric method developed based on the formation of a red-orange peroxovanadate cation from the reaction between H 2 O 2 and vanadate under the acidic medium. , No color change was observed for PDS dark (Figure S3). By contrast, a red-orange color was observed when the PDS light sample was added to the light-yellow vanadate solution, with a main absorption band at 453 nm, providing strong evidence for the formation of H 2 O 2 and the proposed reaction .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the formation of 1 O 2 by spontaneous disproportionation of O 2 •– has long been proposed (R10a–b) . Quantitative determination in the literature revealed that less than 10% of the O 2 produced was in the singlet state, suggesting that this might be an inefficient pathway for 1 O 2 evolution. , In order to confirm the critical role of H 2 O 2 in the PDS system, the presence of H 2 O 2 in PDS dark and PDS light was determined following a spectrophotometric method developed based on the formation of a red-orange peroxovanadate cation from the reaction between H 2 O 2 and vanadate under the acidic medium. , No color change was observed for PDS dark (Figure S3). By contrast, a red-orange color was observed when the PDS light sample was added to the light-yellow vanadate solution, with a main absorption band at 453 nm, providing strong evidence for the formation of H 2 O 2 and the proposed reaction .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of H 2 O 2 in PDS dark and PDS light was determined with a previously reported spectrophotometric method based on the reaction between H 2 O 2 and metavanadate under the acidic medium to produce peroxovanadate with a main absorption peak at around 450 nm using a UV–vis–NIR spectrophotometer (Hitachi U-4100). , …”
Section: Methodsmentioning
confidence: 99%
“…Several analytical methods including spectrographic methods, surface-enhanced Raman spectrographic methods, titrimetric method, and electrochemical methods , have been used to detect SO 2 , but these methods suffer from large instrumentation size, high costs, and complicated and time-consuming processes. Compared with these methods, fluorescence methods are simple, quick, specific, and easily visualized.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are many conventional methods to detect SO 2 and its derivatives, such as titrimetric analysis, , polarography analysis, colorimetry, physical and chemical adsorption, , electrochemical methods, , spectrophotometry, , ion chromatography, , etc. Although these methods possess highly efficient detection capabilities, their intrinsic difficulties (e.g., complex operation, high equipment costs, long response times, etc.)…”
mentioning
confidence: 99%